2010
DOI: 10.3791/2299
|View full text |Cite
|
Sign up to set email alerts
|

Colon Ascendens Stent Peritonitis (CASP) - a Standardized Model for Polymicrobial Abdominal Sepsis

Abstract: Sepsis remains a persistent problem on intensive care units all over the world. Understanding the complex mechanisms of sepsis is the precondition for establishing new therapeutic approaches in this field. Therefore, animal models are required that are able to closely mimic the human disease and also sufficiently deal with scientific questions. The Colon Ascendens Stent Peritonitis (CASP) is a highly standardized model for polymicrobial abdominal sepsis in rodents. In this model, a small stent is surgically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
1
27
0
2
Order By: Relevance
“…We have observed increased levels of TNF-a, IL-1b, IL-6, and IFN-g in CASP-induced sepsis. Similar results were reported by other groups using the CASP model [30,31]. Maier et al [31] observed that serum cytokines (TNF-a, IL-1b, and IL-10) steadily increased during the period of 6 to 18 h after CASP surgery.…”
Section: Discussionsupporting
confidence: 80%
“…We have observed increased levels of TNF-a, IL-1b, IL-6, and IFN-g in CASP-induced sepsis. Similar results were reported by other groups using the CASP model [30,31]. Maier et al [31] observed that serum cytokines (TNF-a, IL-1b, and IL-10) steadily increased during the period of 6 to 18 h after CASP surgery.…”
Section: Discussionsupporting
confidence: 80%
“…A clear signal that we were on the wrong track was that plasma TNFα and IL-1β concentrations were often several logs higher in these models than they were in human sepsis or trauma (Table 1). More recent models that have been employed over the last decade include the commonly used models of polymicrobial abdominal sepsis, including the cecal ligation and puncture (CLP) model [20] and the colon ascendence stent peritonitis model (CASP) [21]. Early on, these models were thought to incite not only the early proinflammatory SIRS component of sepsis, but also, the later anti-inflammatory response, representing the early SIRS-CARS model proposed by Bone and colleagues [22].…”
Section: Inflammation and Survival From Sepsis And Traumamentioning
confidence: 99%
“…Este resuelve uno de los problemas que pueden ocurrir con CLP, que es la formación de un absceso intraabdominal en lugar de un shock séptico por peritonitis. El CASP es un modelo relativamente nuevo y poco común de peritonitis difusa polimicrobiana que reproduce la clínica de una peritonitis aguda [10], además de alterar el flujo sanguíneo cecal con necrosis secundaria de la pared intestinal. La principal desventaja de CASP en comparación con CLP es su mayor complejidad.…”
Section: Figura 2 Absceso En La Superficie Del Hígado Infiltración Dunclassified